2016
DOI: 10.1002/dmrr.2745
|View full text |Cite
|
Sign up to set email alerts
|

Is there still a place for Achilles tendon lengthening?

Abstract: Patients with diabetes and ankle equinus are at particularly high risk for forefoot ulceration because of the development of high forefoot pressures. Stiffness in the triceps surae muscles and tendons are thought to be largely responsible for equinus in patients with diabetes and underpins the surgical rationale for Achilles tendon lengthening (ATL) procedures to alleviate this deformity and reduce ulcer risk. The established/traditional surgical approach is the triple hemisection along the length of the Achil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…23,25 These procedures are not without risk as TAL may result in rupture of the Achilles tendon, whereas GR patients are at risk of losing strength in plantarflexion and nerve injury. 17,29 A comparative analysis of these procedures was performed by Jeng et al, 14 who evidenced that both TAL and GR resulted in an increase in DF, with only GR resulting in a simultaneous increase in PF. Additionally, Ruiz et al 23 reported that patients with high preoperative ROM experienced decreased ankle ROM at final follow-up (mean of 5 years), and that percutaneous TAL had no effect on ankle ROM after TAR.…”
Section: Introductionmentioning
confidence: 99%
“…23,25 These procedures are not without risk as TAL may result in rupture of the Achilles tendon, whereas GR patients are at risk of losing strength in plantarflexion and nerve injury. 17,29 A comparative analysis of these procedures was performed by Jeng et al, 14 who evidenced that both TAL and GR resulted in an increase in DF, with only GR resulting in a simultaneous increase in PF. Additionally, Ruiz et al 23 reported that patients with high preoperative ROM experienced decreased ankle ROM at final follow-up (mean of 5 years), and that percutaneous TAL had no effect on ankle ROM after TAR.…”
Section: Introductionmentioning
confidence: 99%
“…18 Se puede realizar mediante una zetaplastia percutánea abierta o a través de una hemisección triple percutánea. 19 Las ventajas de esta técnica son: bajo índice de infección, curación de herida rápida y carga temprana con uso de yeso, las desventajas son las siguientes: lesión del nervio tibial anterior, del tendón flexor largo del primer dedo y del nervio sural si no se aplica la técnica adecuadamente. 20 La técnica de Barouk es eficaz en la contractura del gastrocnemio en 95%.…”
Section: Discussionunclassified
“…Removing a major deforming force also allows improved intraoperatory mobility and plantigrade positioning. Options include: the Hoke triple hemisection or open Z-plasty for Achilles tendon lengthening, gastrocsoleus release (Strayer technique), transection of gastrocnemius aponeurosis and soleus fascia, occasionally a peroneal longus or tibialis posterior tendon lengthening; postoperative concerns are overcorrection, rupture and poor blood supply [12,17,[26][27][28]. Claw and hammer toes require percutaneous flexor (long ± short) tenotomy procedures [29,30] extensor hallucis longus tendon Z-lengthening or metatarsophalangeal arthrodesis in the opportunity of immobile joints [14,17].…”
Section: Alignment and Complementary Interventionsmentioning
confidence: 99%